2011
DOI: 10.1590/s1519-566x2011000600003
|View full text |Cite
|
Sign up to set email alerts
|

Geographical transition zone of Solenopsis fire ants (Hymenoptera: Formicidae) and Pseudacteon fly parasitoids (Diptera: Phoridae) in the state of São Paulo, Brazil

Abstract: Solenopsis saevissima (Smith) and Solenopsis invicta Buren are the most abundant and widely distributed fire ants in Brazil. The occurrence of the two fire ant species and of their parasitoids Pseudacteon spp. is described for a climatic and phytophysiognomic transition area in the state of São Paulo. Both fire ant species have a parapatric distribution, apparently determined by the climate: S. saevissima predominates in the north part of São Paulo (Aw climate), while S. invicta in the south (Cfa climate). A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The fact that one species of fire ant decapitating fly can attack multiple species of fire ants along its range of distribution has already been mentioned [22,25,63]. It is known that that distribution of these parasitoid flies is mainly determined by its host specificity [64], that those with wider geographical ranges which often attack multiple species of fire ants (usually, too, with wide ranges) [63] and, in this sense, the broader the ranges seems to be the result of parasitoid fly species using multiple host [56]. But particularly, is also known that in a single location multiple Pseudacteon species may coexist and parasitize the same host species [2,9,23].…”
Section: Species Boundariesmentioning
confidence: 99%
“…The fact that one species of fire ant decapitating fly can attack multiple species of fire ants along its range of distribution has already been mentioned [22,25,63]. It is known that that distribution of these parasitoid flies is mainly determined by its host specificity [64], that those with wider geographical ranges which often attack multiple species of fire ants (usually, too, with wide ranges) [63] and, in this sense, the broader the ranges seems to be the result of parasitoid fly species using multiple host [56]. But particularly, is also known that in a single location multiple Pseudacteon species may coexist and parasitize the same host species [2,9,23].…”
Section: Species Boundariesmentioning
confidence: 99%
“…There is limited information about the host preferences of the different species and biotypes of phorid flies. Field assays for host selection demonstrated the preference of the Pseudacteon fly communities for the local fire ant species (89). Laboratory no-choice and pair-wise choice bioassays demonstrated that the Las Flores (Argentina) biotype of P. curvatus obtained from S. richteri populations preferred S. richteri and hybrid fire ants over S. invicta, and the strong preference for S. richteri was retained even after it was successfully reared for many generations on S. invicta (13,42,98).…”
Section: Host Specificity For Solenopsis Complexesmentioning
confidence: 99%
“…Solenopsis saevissima (north climate) and S. invicta (south climate) have a parapatric distribution in the state of São Paulo, Brazil, apparently determined by the climate. Two different communities of decapitating flies were associated with S. saevissima in the north and with S. invicta in the south [51]. The most abundant species in the northern community were Pseudacteon affinis, P. cultellatus, Pseudacteon dentiger, Pseudacteon disneyi, and Pseudacteon fowleri, and in the southern community were P. litoralis, P. pradei, P. tricuspis, and P. wasmanni.…”
Section: Distributionmentioning
confidence: 99%